Clues on Arp 142: The spiral–elliptical merger. Issue 1 (8th July 2019) - Mora, Marcelo D; Torres-Flores, Sergio; Firpo, Verónica; Hernandez-Jimenez, Jose A; Urrutia-Viscarra, Fernanda; Mendes de Oliveira, Claudia
Abstract: Nearby merging pairs are unique laboratories in which one can study the gravitational effects on the individual interacting components. In this manuscript, we report the characterization of selected H ii regions along the peculiar galaxy NGC 2936, member of the galaxy pair Arp 142, an E+S interaction, known as 'The Penguin'. Using Gemini South spectroscopy, we have derived a high enhancement of the global star formation rate (SFR) = 35.9 M⊙ yr −1 probably stimulated by the interaction. Star-forming regions on this galaxy display oxygen abundances that are consistent with solar metallicities. The current data set does not allow us to conclude any clear scenario for NGC 2936. Diagnostic diagrams suggest that the central region of NGC 2936 is ionized by active galactic nucleus (AGN) activity and the eastern tidal plume in NGC 2936 is experiencing a burst of star formation, which may be triggered by the gas compression due to the interaction event with its elliptical companion galaxy: NGC 2937. The ionization mechanism of these sources is consistent with shock models of low velocities of 200–300 km s  −1 . The isophotal analysis shows tidal features on NGC 2937: at inner radii non-concentric (or off-centring) isophotes, and at large radii, a faint excess of the surface brightness profile with respect to de Vaucouleurs law. By comparing the radial velocity profiles and morphological characteristics of Arp 142 with a library of numerical simulations, we conclude that the current stage of the system would be about 50 ± 25 Myr after the first pericentre passage.